ASURANSI SYARIAH: BAGAIMANA KEDEPANNYA? - Riky Soleman; Ririn Dwi Aryanti; Nadia Ulfa (Institut Agama Islam Negeri (IAIN) Ternate, 2023)
Syarikat Takaful Indonesia (Takaful Indonesia) in 1994. The research method used in this research is literature study (Case Study) analyzing from books or various studies that have been done previously. This study aims to critically examine sharia insurance and what will happen in the future? The result of this research is that the birth of Takaful Indonesia as a holding company for PT Asuransi Takaful Keluarga and PT Asuransi Takaful Umum, the first Life and General Sharia Insurance in Indonesia, is the result of commitment and concern for various elements of the nation towards the development of the sharia economy, especially sharia insurance in Indonesia. According to OJK data, as of November 2019, sharia insurance assets against conventional insurance showed a figure of 6.17% or Rp 44.75 trillion (OJK, 2019). To improve and enhance the promotion of the sharia insurance market, support from all parties, be it the government, industry and stakeholders, especially in an effort to increase sharia insurance literacy effectively and massively through socialization of public education.Keywords: Sharia Insurance, Takaful, Life Sharia General Insurance